A qualitative assessment of the impact of a community-embedded intervention on beneficiaries' attitudes and beliefs about adolescent sexual reproductive health in Ebonyi State, Southeast, Nigeria - Chibuike Innocent Agu; Ifunanya Clara Agu; Chinyere Ojiugo Mbachu; Nkoli Ezumah; Obinna Onwujekwe (Reproductive Health, 2024)
Abstract Background Adolescents and their communities in Ebonyi State, Nigeria have poor attitudes and beliefs towards adolescent sexual and reproductive health (SRH). This paper reports on the effects of a community-embedded intervention that focused on creating positive changes in the attitudes and beliefs of adolescents and community members to enhance adolescents’ access to SRH information and services. Methods This study adopted the Qualitative Impact Assessment approach to evaluate the changes in attitudes and beliefs about the SRH of adolescents from the perspectives of the beneficiaries of a community-embedded intervention namely, adolescents, parents, school teachers, and community leaders. The intervention was implemented in six local government areas in Ebonyi State, southeast Nigeria and the evaluation was undertaken four months after the implementation of the interventions commenced. Eighteen (18) interviews were conducted with 82 intervention beneficiaries including: (i) six in-depth interviews with school teachers; (ii) two sex-disaggregated FGDs with parents; (iii) two sex-disaggregated FGDs with community leaders; and (iv) eight sex-disaggregated FGDs with in school and out of school adolescents. A thematic analysis of data was performed with the aid of NVivo software, version 12. Results The community-embedded intervention led to changes in individual attitudes and beliefs, as well as changes in community norms and values concerning adolescent SRH. Adolescents reported that following the community-embedded SRH intervention, they have become more comfortable discussing openly SRH issues with their peers, and they could more easily approach their parents and initiate SRH discussions. The parents of adolescents reported that following the intervention, they have become more willing to discuss sensitive SRH issues with adolescents, and frequently make out time to do so. It was also reported that parents no longer use euphemisms to describe sexual body parts, and community leaders now believe that it is all right to discuss SRH with adolescents. Hence, initiating or having SRH discussions with adolescents is no longer misconceived as encouraging sex, and menstruation in unmarried adolescents is no longer viewed as a sign of promiscuity. Respondents also highlighted changes in community norms of, (i) gendered parental communication of SRH matters, as both mothers and fathers have started discussing SRH issues with their adolescent boys and girls; and (ii) public shaming and discipline of pregnant teenage girls are on the decline. Conclusion The community-based intervention had a positive impact on individual attitudes and beliefs, as well as community and societal values and norms about adolescent SRH. Interventions that take into account community norms and values regarding adolescent SRH should be prioritized to enable the achievement of the SRH-related target of SDG 3.